PALAEOBOTANICAL STUDY OF BURIED PEAT FROM THE MACKENZIE RIVER DELTA AREA, NORTHWEST TERRITORIES - Terasmae, J. (Canadian Journal of Botany, 1959)
A palaeobotanical and palynological study of samples of buried peat from the MacKenzie River delta area, Northwest Territories, has shown that the peat accumulated during an interglacial interval. For reference purposes a study of modern pollen of Rubus chamaemorus L. and of four species of Drosera L. has been made.